Temperature Dependence of Elastic and Ultrasonic Properties of Sodium Borohydride - Singh, Devraj; Mishra, Giridhar; Kumar, Raj; Yadav, Raja Ram (Communications in Physics, 2017)
We present the temperature dependent elastic and ultrasonic properties of sodium borohydride. The second and third order elastic constants of NaBH4 have been computed in the temperature range 0-300K using Coulomb and Born-Mayer potential. The sodium borohydride crystallizes into NaCl-type structure. The computed values of second order elastic constants have been applied to evaluate the temperature dependent mechanical properties such as bulk modulus, shear modulus, tetragonal modulus, Poisson’s ratio and Zener anisotropy factor and ultrasonic velocity to predict futuristic information about sodium borohydride. The fracture to toughness ratio (bulk modulus/shear modulus) in sodium borohydride varied from 1.91 to 1.62, which shows its behavioral change from ductile to brittle on increasing the temperature. Then, ultrasonic Grüneisen parameters have been computed with the use of elastic constants in the temperature regime 100-300K. The obtained results have been discussed in correlation with available experimental and theoretical results. <!–[if !supportLists]–>[1] <!–[endif]–>A. Amudhavalli, M. Manikandan, A. Jemmy Cinthia, R. Rajeswarapalanichamy and K. Iyakutti, Z. Naturforsch. A 72 (2017) 321. <!–[if !supportLists]–>[2] <!–[endif]–>D.Singh, P.K.Yadawa and S.K.Sahu, Cryogenics 50 (2010) 476. <!–[if !supportLists]–>[3] <!–[endif]–>V. Bhalla, D.Singh and S.K.Jain, Int. J. Comput. Mat. Sc. Eng. 5 (2016) 1650012. <!–[if !supportLists]–>[4] <!–[endif]–>S. Kaushik, D. Singh and G. Mishra, Asian J. Chem. 24 (2012) 5655. <!–[if !supportLists]–>[5] <!–[endif]–>D. Chernyshov, A. Bosak, V. Dmitriev, Y. Filmchuk and H. Hagemann, Phys. Rev. B 78 (2008)172104. <!–[if !supportLists]–>[6] <!–[endif]–>H. Hagemann, S. Gomes, G. Renaudin and K. Yvon, J. Alloys Compd. 363 (2004) 126. <!–[if !supportLists]–>[7] <!–[endif]–>Y. Filinchuk, D. Chernyshov and V. Dmitriev, Z. Kristallogr. 223 (2008) 649. <!–[if !supportLists]–>[8] <!–[endif]–>Z.Xiao Dong, J.Z. Yi, Z. Bo, H. Z. Feng and H.Y. Qing, Chin. Phys. Lett. 28(2011)076201. <!–[if !supportLists]–>[9] <!–[endif]–>T. Ghellab, Z. Charifi, H. Baaziz, Ş. Uğur, G. Uğur and F. Soyalp, Phys. Scr. 91 (2016) 045804. <!–[if !supportLists]–>[10] <!–[endif]–>S. Bae, S. Gim, H. Kim and K. Hanna, Appl. Catal. B: Environm.<!–[if !supportNestedAnchors]–><!–[endif]–> 182 (2016) 541. <!–[if !supportLists]–>[11] <!–[endif]–>G. Renaudin, S. Gomes, H. Hagemann, L. Keller and K. Yvon, J Alloys Compd. 375 (2004) 98. <!–[if !supportLists]–>[12] <!–[endif]–>P. Vajeeston, P. Ravindran, A. Kjekshus and H. Fjellvåg, J Alloys Compd. 387 (2005) 97. <!–[if !supportLists]–>[13] <!–[endif]–>S. Orimo, Y. Nakamori, J.R. Eliseo, A. Zuttel and C. M. Jensen, Chem. Rev. 107 (2007) 4111. <!–[if !supportLists]–>[14] <!–[endif]–>A. Istek and E. Gonteki, J. Environ. Bio.7 (2009) 951. <!–[if !supportLists]–>[15] <!–[endif]–>R. S. Kumar and A.L. Cornelinus, Appl. Phys. Lett. 87 (2005) 261916. <!–[if !supportLists]–>[16] <!–[endif]–>E. Kim, R. Kumar, P. F. Weck, A. L. Cornelius, M. Nicol, S. C. Vogel, J. Zhang, M. Hartl, A.C. Stowe, L. Daemen and Y. Zhao, J. Phys. Chem. Lett. B 111 (2007) 13873. <!–[if !supportLists]–>[17] <!–[endif]–>K. Brugger, Phys. Rev. 133 (1964) A1611. <!–[if !supportLists]–>[18] <!–[endif]–>P.B. Ghate, Phy. Rev. 139 (1965) A1666 <!–[if !supportLists]–>[19] <!–[endif]–>S. Mori, Y. Hiki, J. Phys. Soc. Jpn. 45 (1975) 1449. <!–[if !supportLists]–>[20] <!–[endif]–>V. Bhalla, R. Kumar, C. Tripathy and D. Singh, Int. J. Mod. Phys. B 27 (2013) 1350116. <!–[if !supportLists]–>[21] <!–[endif]–>D. Singh, S. Kaushik, S. Tripathi, V. Bhalla and A. K. Gupta, Arab. J. Sci. Eng. 39 (2014) 485. <!–[if !supportLists]–>[22] <!–[endif]–>K. Brugger, Phys. Rev.137 (1965) 1826. <!–[if !supportLists]–>[23] <!–[endif]–>W. P. Mason, Physical Acoustics, vol. IIIB, Academic Press, New York, 1965. <!–[if !supportLists]–>[24] <!–[endif]–>M.P. Tosi, Solid State Physics, vol. 12, Academic Press, New York, 1965. <!–[if !supportLists]–>[25] <!–[endif]–>Y. Nakamori and S. Orimo, J. Alloy Compd.370(2004)271. <!–[if !supportLists]–>[26] <!–[endif]–>D. Singh, D.K. Pandey and P.K. Yadawa, Cent. Eur. J. Phys. 7 (2009) 198. <!–[if !supportLists]–>[27] <!–[endif]–>V. Bhalla, D. Singh, G. Mishra and M. Wan, J. Pure Appl. Ultrason. 38 (2016)23. <!–[if !supportLists]–>[28] <!–[endif]–>D. Singh, S. Kaushik, S.K. Pandey, G. Mishra and V. Bhalla, VNU J. Sc.: Math. Phys. 32(2016)43. <!–[if !supportLists]–>[29] <!–[endif]–>J.P.Watt and L. Peselnick, J.Appl. Phys. 51 (1980) 1525. <!–[if !supportLists]–>[30] <!–[endif]–>S.F.Pugh, Philos.Mag. 45 (1954) 823. <!–[if !supportLists]–>[31] <!–[endif]–>V. Bhalla, D. Singh and S.K. Jain, Int. J. Thermophys. 37(2016)33. <!–[if !supportLists]–>[32] <!–[endif]–>V. Bhalla, D. Singh, S.K. Jain and R. Kumar, Pramana- J. Phys. 86 (2016)135.